REAKSI PASAR TERHADAP PENGUMUMAN CASH DIVIDEND PADA PERUSAHAAN YANG TERGABUNG DALAM INDEKS KOMPAS 100 - Juliana, I Putu Agus Ary Raditya; Candraningrat, Ica Rika (E-Jurnal Manajemen; Vol 9 No 3 (2020)DO - 10.24843/EJMUNUD.2020.v09.i03.p09, 2020)
The purpose of this study is to determine the market reaction to the announcement of cash dividends, by looking at differences in abnormal return and trading volume activity before and after the cash dividend announcement. Dividend announcement is an event that affects the market, because the company provides information to the public. Information provided by the company will influence investors' decision making and will act on that information. The sample of this study amounted to 33 of the 100 companies incorporated in the Kompas 100 index on the Indonesia Stock Exchange (IDX). The data collection method uses non-participant observation, which is document observation. The analysis technique used is Paired-Sample T Test and Wilcoxon-Signed Rank Test. The results showed that there were no differences in abnormal returns and trading volume activity before and after the distribution of cash dividends. Keywords: cash dividend, abnormal return, trading volume activity